The effect of multisector integration communication on empowerment in rural areas - Suryana, Asep; Erlandia, Dedi Rumawan; Suminar, Jenny ratna; Koswara, Iwan; Subekti, Priyo (Jurnal Kajian Komunikasi, 2024)
Background: Empowering impoverished communities has been a long-standing endeavor. However, the persistent prevalence of poverty still affects approximately 25 million individuals (BPS, 2023). Nevertheless, the government continues its relentless efforts to minimize the presence of impoverished families. One of the strategies employed is the implementation of the Family Hope Program (PKH). PKH stands as a program that has effectively fulfilled its mission. Various research studies have been conducted to comprehend the processes, mechanisms, impacts, and societal implications. However, research exploring the cross-sectoral communication aspects, elaborating on the involvement of stakeholders and PKH implementers spanning multiple institutions, remains lacking. Purpose: This research aims to measure the level of influence of multi-sectoral integration communication on the performance of individual PKH implementers. Methods: The employed methodology is an explanatory survey. The surveyed population comprises civil servants engaged in PKH. The population size consists of 80 individuals. Probability sampling is utilized as the sampling technique, with a sample size of 44 respondents, determined using the Slovin method. Hypothesis testing employs Path Analysis. Results: The research findings indicate a significant influence of cross-sectoral communication factors, encompassing organizational member perceptions, organizational strategies, communication climate, media quality, information accessibility, information dissemination, information accuracy, and organizational culture, on the performance of individual PKH implementers. Conclusion: Organizational member performance emerges as a critical aspect for the success of PKH implementation. The research results demonstrate that this performance is influenced by several factors, including information accessibility, media quality, information accuracy, organizational communication climate, organizational culture, information dissemination, and organizational strategies in the execution of the PKH program. Implications: The success of PKH is contingent upon the performance of individual members from collaborating institutions. Enhancing the effectiveness and efficiency of individual performance factors can be achieved by synergizing with cross-sectoral communication components.